Design Of A New Lighting Unit Using TRIZ Approach - Ceren KİRAZ; Hüdayim BAŞAK; Neslihan TOP; İsmail ŞAHİN (Gazi Üniversitesi Fen Bilimleri Dergisi, 2020)
One of the leading roles of interior design is the lighting of the place. Ergonomically designed spaces are made possible by a properly designed lighting. The concept, purpose and functionality that can be designed in the space can be realized by using the right lighting design and usage. Personalized designs, which are popular in recent years, are also an important criterion in the lighting sector. Within the scope of this study, it has been designed by using a new lighting element TRIZ methodology foreseeing that individuals using common living space may need different intensity light at the same time. It is an example of a physical contradiction according to the TRIZ methodology, which is solved by the principles of separation methods in time and space. With the new lighting element designed, adjustable light levels and focal points are provided in shared areas such as dormitory and hotel, which can be solved for different needs of people.